Expression profiling of diabetic and hypertension-associated genes of Malaysian male subjects with coronary heart disease in a hospital in Malaysia - Ahmadloo, Salma (2017)
Coronary Heart Disease (CHD) is still the number-one killer in the world. As for Malaysia, the number of people with CHD has more than tripled in the past 40 years and the figures are still growing. Notably, many of the patients with CHD have at least one modifiable risk factor such as hypertension (HT) and diabetes mellitus (DM). HT and DM stand out as two major modifiable risk factors for CHD and it is well established that the incidence of over 80% of CHD is attributable to these two modifiable risk factors. This study was carried out for the purpose of profiling expression of DM and HT associated genes and identify related biological process and modulated signaling pathways of Malaysian male subjects with CHD from three ethnic group, namely Malay, Chinese and Indian. In order to achieve the goal in group A, four groups of subjects were divided into: 1) 42 healthy subjects; 2) 42 subjects with only DM; 3) 42 subjects with only CHD, and 4) 42 subjects with CHD + DM. The RNA was extracted from blood specimens by mean of commercial extraction kits. The RT2 Profiler™ PCR Array was utilized to determine gene profiling on group 1 and group 2, group 1 and group 3, group 1 and group 4. To validate the results of RT2 profiler™ PCR Array, three of significantly dysregulated genes were selected and validation was conducted through Q-RT-PCR in a larger and independent population. For this purpose, new subjects were divided into: 1) 75 healthy subjects. 2) 75 subjects with DM+CHD. The Same pattern was followed in group B, DM replaced by HT in the groups with the same numbers, to investigate and identify risk genes and modulated pathway/s related to HT which confer risk to CHD development. In order to validate the result in group B, single gene expression profiling was performed between 75 healthy individuals and 75 patients suffering from HT+CHD through Q-RT-PCR (An independent and larger population). In group A, 12 significantly dysregulated genes related to diabetes and Toll-Like receptor signaling pathway were identified which may be a culprit to susceptible diabetic patients to CHD development. In Silico experiments imply a role for inflammatory responses in the circulating leukocytes as a biomarker reflecting initiation of CHD in patients with DM. In group B, 16 significantly dysregulated genes related to hypertension were identified and the RAAS cell signaling pathway was highlighted as a culprit in people suffering from hypertension which may be prone to CHD. In Silico analysis showed that the majority of the identified genes involved in renin-angiotensin regulation and other categories related to renin-angiotensin such as, regulation of blood volume and regulation of blood vessel by renin-angiotensin. In conclusion, some differentially dysregulated genes and modulated pathways were identified which warrant further investigation in the setting of CHD and its risk factors. It is hoped that a greater understanding of genetic predisposition to CHD will unravel clues to its etiology and allow development of novel diagnostic and therapeutic tools to permit targeted interventions to reduce this global health burden.